2018
DOI: 10.3389/fpsyg.2018.00436
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Dissonance and Sickness Absence Among Employees Working With Customers and Clients: A Moderated Mediation Model via Exhaustion and Human Resource Primacy

Abstract: Emotional dissonance, i.e., a discrepancy between required and felt emotions, has been established as a predictor of sickness absence in studies, but little is known about mechanisms that can explain this association. In order to prevent and reduce the impact of emotional dissonance on sickness absence, there is a need for greater attention to variables explaining when and how emotional dissonance is related to sickness absence. The overarching aim of this study was to examine whether emotional dissonance has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 68 publications
(90 reference statements)
2
11
1
Order By: Relevance
“…According to the present study, the dissonance between felt and displayed emotions enhances the likelihood to experience hostile relations that, in turn, are positively associated with mental ill-health conditions (i.e., mental health symptoms). This result corroborated the evidence that the experience of emotional dissonance among workers in client-driven environments could drain their resources and foster emotional exhaustion, which is subsequently associated with higher rates of certified sickness absence [45]. Moreover, the obtained results provided empirical support for the emotion regulation model developed by Grandey and Melloy [13].…”
Section: Discussionsupporting
confidence: 81%
“…According to the present study, the dissonance between felt and displayed emotions enhances the likelihood to experience hostile relations that, in turn, are positively associated with mental ill-health conditions (i.e., mental health symptoms). This result corroborated the evidence that the experience of emotional dissonance among workers in client-driven environments could drain their resources and foster emotional exhaustion, which is subsequently associated with higher rates of certified sickness absence [45]. Moreover, the obtained results provided empirical support for the emotion regulation model developed by Grandey and Melloy [13].…”
Section: Discussionsupporting
confidence: 81%
“…Physical and psychological ill-health have been extensively associated to burnout, including cardiovascular and metabolic disease problems [ 9 , 10 , 11 ], musculoskeletal disorders [ 12 , 13 ], need for recovery [ 14 ] and depressive and sleep symptoms [ 15 , 16 , 17 , 18 ]. Negative occupational outcomes associated with burnout include sickness absences [ 19 , 20 , 21 ], poor job performance [ 22 , 23 ], turnover intentions [ 24 , 25 , 26 ] and worker and patient negative safety outcomes [ 27 , 28 ]. Moreover, burnout is often considered a social problem, especially in welfare states, where national social health systems cover sickness absence and work-related health problems [ 2 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…First, our results are based on cross-sectional data. Although cross-sectional data are still widely used in emotional labor studies (e.g., Molino et al, 2016; Indregard et al, 2018a,b), using time-lagged data would increase the persuasiveness of the suggested causal relationships in this study. Future research would thus benefit from using time-lagged data to analyze the dynamics of employees’ CSR perceptions on their organizational attitudes and behaviors.…”
Section: Discussionmentioning
confidence: 99%